Analisis Faktor Eksternal dan Internal terhadap Perilaku Konsumtif Mahasiswa Jurusan Ilmu Pengetahuan Sosial - Ni Kadek Suryawati; Mahmudah Hasanah; Muhammad Rahmattullah; Syaripudin Bahar (Jurnal Syntax Admiration, 2024)
The purpose of this study is to evaluate the influence of internal and external factors on consumptive behavior. This problem is focused on the high level of consumptive behavior among students caused by factors that come from outside and within the individual. The research method used is descriptive research with a quantitative approach. The sample was taken using the Purposive Random Sampling technique as many as 271 students of the Department of Social Sciences. The data collection method uses questionnaires, observations, and documentation from students as well as references from journals, books, and other relevant sources. Descriptive statistical analysis, classical assumption test, multiple regression analysis, partial test (t-test), simultaneous test (f-test), and determination coefficient test (R2) were used to analyze the research data. The results showed that there was a multiple regression equation showing that Y = 5.026 + 0.438X1 + 0.267X2. Based on the hypothesis test, the significance value (Sig) of 0.000 is greater than the probability of 0.05, so it can be concluded that the external factor (X1) and internal factor (X2) have a significant and positive influence on the consumptive behavior (Y) of students of the Department of Social Sciences.